Front Cover: Hexanuclear Niobium Cluster Alcoholates – First Representatives with Isopropanolato Ligands (Z. Anorg. Allg. Chem. 20/2022). Issue 20 (17th October 2022) - Schröder, Florian; Köckerling, Martin
Abstract : The cover picture shows the nucleophilic attack of alkoxides on the hexanuclear cluster compound, which carries halide (iodido and chloride) ligands, [Nb6 Cl12 I6 ] 2− . Li(OC3 H7 ) is used as strongly basic agent in solution‐based chemical reactions near room temperature. The first representatives of cluster compounds with isopropanolato ligands on the inner coordination sites of the octahedral metal atom cores are formed.(DOI: 10.1002/zaac.202200241 ).